Heike Deckert-Peaceman und Gerold Scholz: Vom Kind zum Schüler. Diskurs-Praxis-Formationen zum Schulanfang und ihre Bedeutung für die Theorie der Grundschule. - Büker, Petra (Zeitschrift für Grundschulforschung)

Bildungshäuser als "Dritter Raum" im Übergang zwischen Kita und Grundschule - Kritische Blicke auf ein Jahrzehnt Intensivkooperation - Höke, Julia; Bührmann, Thorsten; Büker, Petra; Hummel, Rebecca; Meser, Kapriel; Miller, Susanne; Stölner, Robert (Zeitschrift für Grundschulforschung)

Bildungshäuser als interinstitutionelle Bildungsräume für Kinder und pädagogische Fachkräfte. Wie können Kinder, Fachkräfte und die Übergangsgestaltung von Kooperationen in Bildungshäusern profitieren? Keynote an der Netzwerktagung "Qualität vor Ort", einer Gemeinschaftsaktion der Deutschen Kinder- und Jugendstiftung (DKJS), des Bundesministeriums für Familie, Senioren, Frauen und Jugend (BMFSFJ) und der Jacobs Foundation zur Stärkung frühkindlicher Bildung. Bildungshaus Hahle / Stade - Büker, Petra
Angegebener Monat: Dezember 2017

Inklusion vom Kind aus denken. Die neue Study-Edition für die Aus- und Weiterbildung von pädagogischen Fach- und Lehrkräften. Öffentliche Workshoptagung für Akteure aus Wissenschaft und Praxis. Universität Paderborn - Büker, Petra
Februar und November 2017

Partizipation von Kindergarten- und Grundschulkindern an Übergangsgestaltung, Übergangsforschung und am Transfer in optimierte Praxis. Erfahrungen aus einer Kinderbefragungsstudie im Rahmen des Modellprojekts "buddY". Beitrag im Rahmen des Symposiums: Perspektiven des Transfers von Forschungsbefunden im Übergang Kindergarten - Grundschule an der 26. Jahrestagung der Kommission Grundschulforschung und Pädagogik der Primarstufe an der Universität Landau - Büker, Petra
September 2017

Immigrant Children as ‘Experts’ of their Culture?! Addressing cultural diversity in kindergarten and primary education: children’s and teacher’s perspectives. Symposiumsbeitrag im Rahmen der 27 th EECERA conference - European Early Childhood Research Association. Universität Bologna, Italien - Büker, Petra; Hüpping, Birgit
August 2017

Kinder stärken für das Aufwachsen in pluralen Lebenswelten. Keynote an der Schulanfangstagung des Instituts für Qualitätsentwicklung an Schulen Schleswig Holsteins (IQSH): Von Anfang an: Kinder stärken – Vielfältigkeit leben. Kiel - Büker, Petra
Juli 2017

Kita und Grundschule auf dem Weg zur Partnerschaft: Was macht die Qualität der Kooperation aus? Einführungsvortrag im Rahmen der Auftaktveranstaltung zur Eröffnung des Weiterbildungsprogramms für pädagogische Fach- und Lehrkräfte zur Qualitätsentwicklung im Übergang mit dem Paderborner Qualitätsstern. In Kooperation mit dem Bildungsbüro Kind und Ko Paderborn sowie dem Jugendamt der Stadt Detmold - Büker, Petra
In Kooperation mit dem Bildungsbüro Kind und Ko Paderborn sowie dem Jugendamt der Stadt Detmold. Juni 2017

Forschen – Irritieren – Reflektieren: Das Paderborner Zentrum für KinderBildungsForschung (KiBi-Z) unterstützt Studierende beim Lernen in der Praxis. Symposiumsbeitrag im Rahmen des 2. Internationalen Kongresses "Lernen in der Praxis - Professionalisierungsprozesse im Kontext schulpraktischer Studien in der Lehrerbildung" an der Ruhr-Universität Bochum - Büker, Petra
März 2017

„Ich kann das Forschungsgedöns ja doch gebrauchen!“ – Zur Konzeption und Evaluation der Lehrveranstaltungen im Praxissemester an der WWU Münster - Bloh, Bea; van Ophuysen, Stefanie; Behrmann, Lars; Homt, Martina; Schürer, Sina

“As a person, I feel I’ve changed pretty immensely”: Sojourners’ aspirations and self-perceived achievements - Müller, Mareike (The Canadian Modern Language Review)
This article explores the interplay between learners’ linguistic and personal objectives as well as evaluations of their achievements in study-abroad contexts, an area that has thus far remained widely unexplored given the prevalence of product-oriented, outcomes-based research. The study draws on the case of one Canadian student of German who studied abroad at a German university for one year. To adopt an emic perspective, the data gained from a learning history questionnaire, semi-structured interviews, and e-journals were analyzed and interpreted within the framework of narrative analysis. The results show not only that learners’ sojourn objectives may be complex, dynamic, and contradictory in nature but also that they need to be examined beyond their face value, as they are entangled with learners’ negotiations of desirable subject positions and attempts to integrate their sojourn experiences, successes, and frustrations in a coherent and positive life narrative.
Keywords: individual differences; learner beliefs; narrative analysis; sojourn objectives and evaluations; study abroad

Narrating the sound of self: The role of pronunciation in learners’ self-constructions in study-abroad contexts - Müller, Mareike; Schmenk, Barbara (International Journal of Applied Linguistics)
This paper discusses the findings of an empirical study that explores the relationship between study-abroad experiences, learner identity, and pronunciation. We argue that the role of pronunciation as a personal domain of meaning-making warrants more attention than it has hitherto received. To this end, we investigate the narratives of Canadian learners, studying abroad in Germany, in relation to discourses of language learning, culture, and identity, using a Critical Discourse Analysis approach. Our data, which we gained from semi-structured interviews and e-journals, shows that learners’ perceptions of pronunciation are closely linked to their views of the native-speaker ideal, impacting their self-constructions and interpretations of learning experience. In conclusion, we argue for a more differentiated understanding of pronunciation and its implications for language teaching and study abroad.
Keywords: learner identity; study abroad; pronunciation; native-speaker ideal; critical discourse analysis

Digitale Bildung – eine neue Perspektive auf Bildungsgerechtigkeit? - Eickelmann, Birgit; Drossel, Kerstin (Dreizehn – Zeitschrift für Jugendsozialarbeit)

Zum Stellenwert neuer Technologien für die individuelle Förderung im Deutschunterricht in der Grundschule - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried (Individualisierung im Grundschulunterricht: Anspruch, Realisierung und Risiken)

Computational Thinking als internationales Zusatzmodul zu ICILS 2018 – Konzeptionierung und Perspektiven für die empirische Bildungsforschung - Eickelmann, Birgit (Tertium Comparationis. Journal für International und Interkulturell Vergleichende Erziehungswissenschaft)

Digitalisierung. Neue Herausforderungen für Schulen und Schulaufsicht - Eickelmann, Birgit (Neue Deutsche Schule. Die Zeitschrift der Bildungsgewerkschaft)

Digitale Kompetenzen im internationalen Vergleich. Welche Impulse geben die Studien ICILS 2013 und ICILS 2018? - Eickelmann, Birgit (Zeitschrift Schul-Management)

Lernende Schulen in der digitalen Welt – Herausforderungen und Perspektiven - Eickelmann, Birgit (Basisartikel im Heft 'Digitalisierung in der Schule'. Lernende Schule)

Kompetenzen in der digitalen Welt. Konzepte und Perspektiven - Eickelmann, Birgit

Lehren und Lernen mit digitalen Medien - Zielsetzungen, Rahmenbedingungen und Implikationen für die Schulentwicklung - Eickelmann, Birgit; Gerick, Julia (Lehren und Lernen mit digitalen Medien. Strategien, internationale Trends und pädagogische Orientierungen)

Computer Literacy im schulischen Kontext – eine internationale Perspektive - Eickelmann, Birgit (Bildung im Digitalen Zeitalter - Bilanz und Perspektiven)

Computer- und informationsbezogene Kompetenzen in der IEA-Studie ICILS 2013 und der Zusammenhang mit der Lesekompetenz - Eickelmann, Birgit; Drossel, Kerstin (Medienimpulse)

Abschlussbericht im Rahmen der wissenschaftlichen Begleitung der Evaluation des Projekts „Lernen mit digitalen Medien“ in Schleswig-Holstein - Gerick, Julia; Eickelmann, Birgit

Digitale Medien in Schule und Unterricht – Herausforderungen für die Schulentwicklung - Gerick, Julia; Eickelmann, Birgit; Rolff, Hans-Günter (Journal für Schulentwicklung)

Gelingensbedingungen für den Transfer schulischer Innovationen mit digitalen Medien. Ergebnisse aus einem Modellprojekt - Gerick, Julia; Eickelmann, Birgit; Ramm, Gesa; Kühn, Thore-Olaf (Journal für Schulentwicklung)

Schulische Medienkonzepte als Instrument der Schulentwicklung - Eickelmann, Birgit (Journal für Schulentwicklung)

Digitale Medien in Schule und Unterricht. Herausforderungen für die Schulentwicklung [Themenheft] (Journal für Schulentwicklung)

Lernaktivitäten mit digitalen Medien im Fachunterricht der Sekundarstufe I im Bundesländervergleich mit besonderem Fokus auf MINT-Fächer - Eickelmann, Birgit; Lorenz, Ramona; Endberg, Manuela (Schule digital – der Länderindikator 2017. Schulische Medienbildung in der Sekundarstufe I mit besonderem Fokus auf MINT-Fächer im Bundesländervergleich und Trends von 2015 bis 2017)

Unterrichtliche Nutzung digitaler Medien durch Lehrpersonen in der Sekundarstufe I im Bundesländervergleich und im Trend von 2015 bis 2017 - Lorenz, Ramona; Endberg, Manuela; Eickelmann, Birgit (Schule digital – der Länderindikator 2017. Schulische Medienbildung in der Sekundarstufe I mit besonderem Fokus auf MINT-Fächer im Bundesländervergleich und Trends von 2015 bis 2017)

Schule digital – der Länderindikator 2017. Schulische Medienbildung in der Sekundarstufe I mit besonderem Fokus auf MINT-Fächer im Bundesländervergleich und Trends von 2015 bis 2017

School-level predictors for the use of ICT in schools and students’ CIL in international comparison - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried (Large-scale Assessments in Education)

Predictors of teachers’ use of ICT in school – the relevance of school characteristics, teachers’ attitudes and teacher collaboration - Drossel, Kerstin; Eickelmann, Birgit; Gerick, Julia (Education and Information Technologies)

ICT use in mathematics lessons and the mathematics achievement of secondary school students by international comparison: Which role do school level factors play? - Eickelmann, Birgit; Gerick, Julia; Koop, Christian (Education and Information Technologies)

Teachers‘ attitudes and beliefs regarding ICT in teaching and learning in European countries - Eickelmann, Birgit; Vennemann, Mario (European Educational Research Journal)
In the debate on the integration of information and communication technologies (ICT) into schools, the beliefs and attitudes of teachers towards ICT in teaching and learning have always been regarded as central criteria for successful implementation of new technologies. In this context, a study in 2013 by the International Association for the Evaluation of Educational Achievement, IEA, provided insights into teachers’ beliefs regarding ICT and showed that perceptions of the pedagogical advantages of technologies differ between countries. With regard to this finding, this paper seeks to determine whether there is a typology of teachers with different attitudes towards the potential of ICTs for learning. This question is addressed by conducting latent class analyses on a sample of teacher data from three European countries – the Czech Republic, Germany and Norway. Furthermore, the paper investigates how the use of computers by teachers varies between the groups to which these teachers can be assigned. In doing so the research reported at hand connects, arguably for the first time, representative data on teacher typologies of attitudes towards and beliefs about ICT in teaching and learning with data on computer use in schools.

The international computer and information literacy study from a European perspective: Introduction to the Special Issue - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried (European Educational Research Journal)
The International Computer and Information Literacy Study (ICILS 2013) provides, for the first time, information about students’ computer and information literacy (CIL), as well as its acquisition, based on a computer-based test for students and background questionnaires. Among the 21 education systems that participated in ICILS 2013, there are 12 European countries, making secondary comparative in-depth analyses at a European level particularly fruitful. Accordingly, while the four articles in this Special Issue each deal with different topics and adopt different methodologies, they all share a common element and provide European comparisons in the ICILS context. The editorial in turn outlines the aim of the ICILS 2013 study and its relevance for European education research as well as its contextual framework and approach to the measurement of students’ CIL. The potential and challenges of such large-scale assessment studies are also discussed.

The Use of Tablets in Secondary Schools and Its Relationship with Computer Literacy - Drossel, Kerstin; Eickelmann, Birgit (Tomorrow's learning: involving everyone. Learning with and about technologies and computing)

Schulische Medienkompetenzförderung - Eickelmann, Birgit (Medienkompetenz. Herausforderung für Politik, politische Bildung und Medienbildung)

Понять, как они тикают [Verstehen, wie sie ticken]. Interview on CLIL conducted by Ирина Долженко [Irina Dolzhenko] on behalf of sib.fm - Dolzhenko, Irina; Rumlich, Dominik

Unter welchen Voraussetzungen kooperieren Grundschullehrkräfte im inklusiven Unterricht? Eine Studie zu den Bedingungen der Kooperationsbereitschaft von Grundschullehrerinnen und -lehrern im inklusiven Unterricht - Hellmich, Frank; Hoya, Fabian Karl; Görel, Gamze; Schwab, Susanne (Empirische Sonderpädagogik)
Als wichtige Bedingungen für die Realisierung inklusiven Unterrichts in der Grundschule gelten Kooperationen von Grund- und Sonderschullehrkräften. Bislang ist wenig darüber bekannt, unter welchen Voraussetzungen Grundschullehrkräfte Bereitschaft zur Kooperation im inklusiven Unterricht zeigen. Vor diesem Hintergrund haben wir 168 Grundschullehrkräfte einerseits zu ihrer Kooperationsbereitschaft im inklusiven Unterricht und andererseits zu ihren Einstellungen zur Inklusion und zur Teamarbeit, ihren Erfahrungen aus dem integrativen bzw. inklusiven Unterricht sowie ihren Selbstwirksamkeitsüberzeugungen für die Gestaltung des inklusiven Unterrichts befragt. Die Ergebnisse aus einem Strukturgleichungsmodell geben Hinweise auf die Bedeutungen der Einstellungen zur Teamarbeit und der Erfahrungen aus dem integrativen bzw. inklusiven Unterricht für die Kooperationsbereitschaft der Grundschullehrkräfte. (DIPF/Orig.)

Motivation für die Beschäftigung mit Inklusion während des Studiums bei Studierenden des Lehramts an Grundschulen - Hellmich, Frank; Görel, Gamze; Schwab, Susanne (Profession und Disziplin - Grundschulpädagogik im Diskurs)

Erfahrungen, Einstellungen und Motivation von Studierenden des Grundschullehramts in Hinblick auf den inklusiven Unterricht. - Görel, Gamze; Hellmich, Frank (Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik)

Self-efficacy of prospective Austrian and German primary school teachers regarding the implementation of inclusive education - Schwab, Susanne; Hellmich, Frank; Görel, Gamze (Journal of Research in Special Educational Needs)

Einstellungen von Kindern gegenüber Peers mit sonderpädagogischem Förderbedarf als Bedingungen der sozialen Partizipation im inklusiven Unterricht der Grundschule - Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca (Inklusiver Unterricht in der Grundschule)

Primary school students’ implicit theories and their reading motivation. The role of parents’ and teachers’ effort feedback - Hellmich, Frank; Hoya, Fabian Karl (Zeitschrift für Psychologie)
Abstract. Parents’ and teachers’ effort feedback is considered to be an important prerequisite for children’s implicit theories of intelligence and their academic self-concepts as well as for their learning and achievement motivation. Therefore, our study examines whether differences in N = 685 primary school students’ implicit theories, their reading self-concepts, and their reading motivation can be predicted by their perceptions of their parents’ and teachers’ effort feedback on reading processes. The results of a structural equation model show that children’s perceptions of their parents’ effort feedback predict their implicit theories, their reading self-concepts, and their reading motivation. The correlation between children’s perceived parental effort feedback and their intrinsic reading motivation is mediated by their implicit theories. Children’s implicit theories and their reading motivation cannot be predicted by their perceptions of their teachers’ effort feedback.

Empirische Arbeit: Wahrgenommenes positives Feedback zu Leseprozessen in Elternhaus und Schule im Zusammenhang mit der Lesemotivation von Kindern im Grundschulalter - Hellmich, Frank; Hoya, Fabian Karl (Psychologie in Erziehung und Unterricht)

Soziale Selbstkonzepte von Kindern im Grundschulalter und ihre Einstellungen gegenüber Peers mit Förderbedarf in der sozial-emotionalen Entwicklung - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik)

Inklusiver Unterricht in der Grundschule

Decision Taking, Confidence and Risk Management in Banks from Early Modernity to the 20th Century

Human agency at work: An active approach towards expertise development - Goller, Michael
Michael Goller gives a structured overview of the current discourses of human agency in relation to professional learning and development. Based on this discussion, the author develops a theoretical framework including human agency as an individual feature (i. e., a disposition) as well as a set of self-initiated and goal-directed behaviours that are assumed to affect employees’ learning and development (e. g., crafting of new work experiences). He then further specifies this theoretical framework and investigates it empirically in the domain of geriatric care nursing. Based on the findings of the three empirical studies conducted, the author discusses the relevance of human agency for the development of professional expertise of geriatric care nurses. The work received the American Educational Research Association (AERA) Workplace Learning SIG 2017 Dissertation of the Year Award.
Keywords: Workplace learning; Agency; Expertise

Intuition as Crucial Component of Professional Competence: Its Relevance for Competence-based Vocational and Professional Education and Training - Harteis, Christian (Competence-based Vocational and Professional Education)